Les « Cent-Jours » de Chabert - Joëlle Jonquières (Temporalités)
Submitting Colonel Chabert to a lexical analysis reveals a temporal construction based on the contrast between past and present. Replacing that opposition within the social and historical context of the novel transforms it into a contrast between the First Empire and the Restoration. This temporal duality in turn reveals a discursive structure based on the ancient myth of Ulysses. By comparing the main features of Chabert and Ulysses, we discover what differentiates Balzac hero caught in the web of time, from the mythical hero, untouched by temporality like all the great characters of history such as Napoleon Bonaparte paradoxically are. Sociological analysis allows us to extract from History the elements of phenomenology and the social construction of both a common reality and a differentiated reality wich delimit the common universe people belong to and the temporal sub-universes which must be reinterpreted in the light of social change. Chaberts madness is that he is unable to reinterpret the latter or rather that he refuses to interpret anything.